Development and evolution of the collopallium in amniotes: a new hypothesis of field homology. - Butler, AB; Molnár, Z (2002)
Embryological development is uniquely positioned to illuminate both hodology in adult brains and its inherited genetic bases. The lateral corner of the lateral ventricle in mammals is a particularly crucial region where cell migration patterns, transiently formed connections, axonal growth kinetics, and fasciculation patterns are complex and interactive. Based on hodology, the sauropsid anterior dorsal ventricular ridge (ADVR) has been proposed as the homologue on a one-to-one basis of the mammalian lateral neocortex (LNC), the basolateral amygdalar complex (BLA), or the claustrum-endopiriform nucleus (CE). Data on gene expression patterns during development have indicated ADVR homology with parts of the latter two structures rather than with LNC. Collothalamic nuclei (the set of dorsal thalamic nuclei that receive their predominant input from the midbrain roof) project to part of BLA and to LNC. Recent findings demonstrate a complex pattern of mutually overlapping but noncongruent gene expression territories and collothalamic projections, which suggests a new, collopallial field hypothesis that the ADVR is homologous as a field to all three structures LNC, BLA, and CE. This hypothesis accounts for current hodological and developmental data as well as for lack of a CE in monotremes and for an abnormal subcortical lamina of gray matter that results from a genetic abnormality in humans.